A New Design Of Three Phase Transformer Under Nonlinear Load Condition - Azizan, Muhammad Mokhzaini (2013)
Usage of nonlinear loads such as electronic device causes current at power distribution system to be distorted and contains harmonic. Effect of current harmonic is overheating of transformer at power distribution system. Overheating is caused by the increase of copper power loss at winding wire and core power loss (hysteresis and eddy current). As result insulation is degraded and risk of permanent malfunction at transformer (burn). Existing solutions regarding this problem is by reducing and increasing transformer capacity and the reduce of transformer loading. This gives bigger area to sustain effect of current harmonic. This thesis proposes a new design three phase transformer without changing of capacity. This can be achieved by resizing of winding wire and core. This transformer is specially design for nonlinear loading with current harmonic content (THDi) of 40%. Resizing method is performed at transformer material of winding wire and magnetic core in order to sustain the additional loss caused by current harmonic. It also reduces copper loss at winding wire and hysteresis loss at transformer core. Resizing technique is based on the determination of sizing factor with the function of THDi that is proportion to rated transformer operating temperature. It is the ratio between transformer operating temperatures under nonlinear loading. Experimental result on a three phase 2 kVA, 415V, 50Hz transformer yields sizing factor of 0.012 and 0.075 for winding wire and core respectively By utilizing the determined sizing factor, a new transformer is designed with winding wire AWG 19 and core with dimension 1358cm2. It is able to sustain additional transformer power loss caused by current harmonic as much 40% THDi at rated operating temperature 55°C. This design method can be improved by considering selection of material with higher permeability to the extent design dimension of transformer is made smaller (more economical).